The New Typography - Tschichold, Jan; Hendel, Richard; Kinross, Robin; McLean, Ruari (Berkeley, CA : University of California Press, 2020)
Since its initial publication in Berlin in 1928, Jan Tschichold's The New Typography has been recognized as the definitive treatise on book and graphic design in the machine age. First published in English in 1995, with an excellent introduction by Robin Kinross, this new edition includes a foreword by Rich Hendel, who considers current thinking about Tschichold's life and work.
Frontmatter -- CONTENTS -- TRANSLATOR'S FOREWORD -- REVISIONS TO DIE NEUE TYPOGRAPHIE -- Introduction to the English-Language Edition -- Foreword to the 2006 Edition -- THE NEW TYPOGRAPHY -- CONTENTS -- Introduction -- The new world view -- The old typography (1440-1914) , retrospective view and criticism -- The new art -- The history of the new typography -- The principles of the new typography -- Photography and typography -- New typography and standardization -- The typographic symbol -- The business letterhead -- The half letterhead -- Envelopes without windows -- Window envelopes -- The postcard -- The postcard with flap -- The business card -- The visiting-card -- Advertising matter (slips cards leaflets prospectuses catalogues) -- The typo-poster -- The pictorial poster -- Labels, plates, and frames -- Advertisements -- The periodical -- The newspaper -- The illustrated paper -- Tabular matter -- The new book -- Bibliography -- List of Addresses
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 01. Okt 2020).
JSTOR
Keywords: Printing; HISTORY / Europe / General; ART / General; Printing